2021
DOI: 10.1039/d1gc02439f
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrin and single atom featured reticular materials: recent advances and future perspective of solar-driven CO2reduction

Abstract: The release of large volumes of anthropogenic CO2 coupled with growing exploitation of fossil fuels has led to very serious issues such as global warming and energy crisis in the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 257 publications
0
32
0
Order By: Relevance
“…It is worth reiterating that the incorporation of metal SAs into a semiconductor modifies its energy band structure (VB and CB positions); thus, the energy band levels of semiconducting support can be modified to promote a specific redox reaction. [159] For example, Jin et al conducted a theoretical study on the effect of incorporating metal SAs in TiO 2 , they found that it changes the CB minimum and VB maximum of TiO 2 . [160,161] According to their study, the CB minimum of TiO 2 and c) PDOS of CO 2 and adsorption sites in Au SA /Cd 1-x S; and CO 2 adsorption on d) pristine CdS 1-x and e) Au SA /CdS 1-x , and f) PDOS of CO 2 and adsorption sites in Au SA /CdS 1-x .…”
Section: Role Of H 2 O Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth reiterating that the incorporation of metal SAs into a semiconductor modifies its energy band structure (VB and CB positions); thus, the energy band levels of semiconducting support can be modified to promote a specific redox reaction. [159] For example, Jin et al conducted a theoretical study on the effect of incorporating metal SAs in TiO 2 , they found that it changes the CB minimum and VB maximum of TiO 2 . [160,161] According to their study, the CB minimum of TiO 2 and c) PDOS of CO 2 and adsorption sites in Au SA /Cd 1-x S; and CO 2 adsorption on d) pristine CdS 1-x and e) Au SA /CdS 1-x , and f) PDOS of CO 2 and adsorption sites in Au SA /CdS 1-x .…”
Section: Role Of H 2 O Moleculesmentioning
confidence: 99%
“…It is worth reiterating that the incorporation of metal SAs into a semiconductor modifies its energy band structure (VB and CB positions); thus, the energy band levels of semiconducting support can be modified to promote a specific redox reaction. [ 159 ] For example, Jin et al. conducted a theoretical study on the effect of incorporating metal SAs in TiO 2 , they found that it changes the CB minimum and VB maximum of TiO 2 .…”
Section: Sacs For Photocatalytic Co2 Reductionmentioning
confidence: 99%
“…After the electronic equilibrium is established at the interface, the photogenerated electrons in the semiconductor will pass through the Schottky barrier and transfer to the metal particles ( Gao et al., 2020a ). This charge transfer behavior across the metal-semiconductor interface can be inherited by the SAPs ( Gao et al., 2020a ; Gopalakrishnan et al., 2021 ). It was demonstrated that, when the metal SAs were contacted with the semiconductor substrate, efficient charge transfer behaviors could be expected due to the interfacial barrier ( Meng et al., 2019 ; Wang et al., 2019a ).…”
Section: Current Research Progress On Sapsmentioning
confidence: 99%
“…On the other hand, the derivatized porphyrins can be used as building blocks to construct porous polymers, such as coordination polymers and porous organic polymers (POPs) [ 16 , 17 , 18 , 19 ]. The above-mentioned factors are meaningful to effectively modulate the catalytic features of porphyrins, making them excellent candidate catalysts for many processes, such as organic chemical reactions, ORR, HER, CO 2 reduction reaction (CO 2 RR), and of course, OER [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%